Public Support for Large Companies to Prevent the Effects of the Covid-19 Pandemic – Study Based on the Example of the Guarantee of the PLG FGP Guarantee Line – Legal and Economic Aspects - Kowalski, Dariusz; Zając, Adam (Journal of Finance and Financial Law, 2023)
The purpose of the article/hypothesis: The purpose of the article is to determine whether, taking into account the current legal framework determining the state role in the economy, it is advisable to support large enterprises in relation to preventing the effects of the COVID-19 pandemic. The analysis will be conducted based on one of the types of guarantees - PLG FGP guarantee line. Methodology: In order to achieve the assumed goals, the analysis was based on non-reactive research, consisting in the assessment of available information. It included studies of normative acts, official statistical data and industry reports and analyses. Two basic research methods were used, namely legal dogmatic and comparative analyses. Results of the research: Based on the conducted research, it can be concluded that taking into account the characteristics of economic difficulties resulting from the COVID-19 pandemic (i.e. a decrease in demand for goods and services, reduced mobility of the population, limited supply caused by disruption of supply chains and absence of employees at the workplace), it is justified to support sector of large enterprises, because these problems concern both the SME sector and large enterprises to a similar extent. However, it is reasonable to direct the aid because financing was also used by enterprises that were not affected by the crisis.